Islamic religious education and radicalism in Indonesia: strategy of de-radicalization through strengthening the living values education - Syamsul Arifin (Indonesian Journal of Islam and Muslim Societies, 2016)
In Indonesian national system of education, Islamic religious education is compulsory for all levels of formal education. Taking into account such a position, Islamic religious education is potentially strategic in responding to some of the main issues in religious life. One issue examined in this paper is radicalism that continues to overshadow the dynamics of religious life in In- donesia. Although numerous attempts (mainly security approach) to eradi- cate radicalism have been taken, radicalism is still a prominent problem in Indonesia. This paper argues that Islamic religious education should be em- powered in order to reduce the spread of radicalism. In order to bring these ideas into reality, this paper further offers Living Values E education (LVE) as a theoretical framework to develop Islamic religious education which is com- patible with this goal. Pendidikan agama Islam dalam sistem pendidikan nasional di Indonesia merupakan salah satu materi yang wajib diajarkan dalam institusi pendidikan formal mulai dari jenjang pendidikan dasar sampai ke jenjang pendidikan tinggi. Dengan mempertimbangkan posisinya yang demikian, pendidikan agama Is- lam memiliki potensi strategis untuk merespons beberapa persoalan utamanya dalam kehidupan agama. Salah satu persoalan yang hendak dikaji dalam tulisan ini adalah radikalisme yang terus membayangi kehidupan umat beragama di Indonesia. Meskipun telah dirancang berbagai upaya untuk membendung radikalisme terutama dengan menggunakan pendekatan keamanan, radikalisme ternyata masih eksis di Indonesia. Tulisan ini menawarkan pendidikan agama Islam sebagai salah satu institusi pendidikan yang perlu diberdayakan untuk membendung arus radikalisme. Untuk mewujudkan pemikiran tersebut, tulisan ini selanjutnya menawarkan living values education (LVE) sebagai suatu kerangka teoritik untuk mengembangkan pendidikan agama Islam.